1997
DOI: 10.1073/pnas.94.7.3206
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the extreme 5′-terminal sequences of the RNA genomes of GB virus C/hepatitis G virus

Abstract: The extreme 5-terminal sequences of the GB virus C͞hepatitis G virus (GBV-C͞HGV), containing elements essential for regulation of viral gene expression and replication, have not been determined. By using a RNA-ligasemediated RACE (rapid amplification of the cDNA ends) procedure, we have cloned the extreme 5-terminal sequences of the viral genome from the serum of three Taiwanese patients. Sequence analysis of the 5 noncoding region in alignment with one West African and two American isolates showed that (i) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Thus, among our patients, the NS3 sequence was highly conserved. Consequently, primers from this region appeared to be more efficient in the identification of different GBV-C/HGV genotypes than those derived from the 5Ј UTR region (exhibiting high sequence divergence between different isolates) [Hsieh et al, 1997]. No clear pattern emerged, and GBV-C/HGV infection was found in heterogeneous groups of hematological diseases with possibly different aetiologies.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, among our patients, the NS3 sequence was highly conserved. Consequently, primers from this region appeared to be more efficient in the identification of different GBV-C/HGV genotypes than those derived from the 5Ј UTR region (exhibiting high sequence divergence between different isolates) [Hsieh et al, 1997]. No clear pattern emerged, and GBV-C/HGV infection was found in heterogeneous groups of hematological diseases with possibly different aetiologies.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, analysis of these isolates using the 400 bp envelope region sequence suggests that the definition of three HGV genotypes based on the entire genome might be similar to our grouping. Other groups have also suggested similar classification of HGV into two to five genotypes, subtypes or groups based on their analyses of 5h UTR region (Muerhoff et al, 1996 ;Fukushi et al, 1996 ;Ding et al, 1997 ;Hsieh et al, 1997 ;Mukaide et al, 1997) or NS3 helicase region sequences (Kao et al,1996). Furthermore, Mukaide et al (1997) also identified ' genotype '-specific restriction sites, ScrFI and BsmFI, and developed restriction polymorphism analysis.…”
Section: Sequence Variability In the E2 Variable (Ev) Region Of Hgvmentioning
confidence: 99%
“…1a). When analysing all sequenced clones, it was observed that most of the substitutions occurred within the three regions associated with specific polymorphisms in the 59 UTR, strongly correlated with phylogenetic clustering of variants (Hsieh et al, 1997;Smith et al, 1997), herein named V-1, V-2 and V-3 (Fig. 1a).…”
mentioning
confidence: 99%